IMPLEMENTASI PROGRAM PEMBERDAYAAN RUMAH TANGGA SANGAT MISKIN - Jadmika Sufiadi; Irwan Noor; Suryadi . (REFORMASI, 2015)
The title of this study is The Implementation of the Very Poor Households Empowerment Program. The objective of this study is to describe and analyze the implementation of the very poor households empowerment program in the Provincial Marine Affairs and Fisheries of East Java and also the supporting as well as inhibiting factors in implementing this program in the provincial Marine Affairs and Fisheries of East Java. A qualitative descriptive approach is used as the research method in this study. The Miles and Hubberman methode is used as the data analysis technique. The factors that can determine the success of the program implementation is the very poor households’ participation as the beneficiaries of the program; integrated communications established by the Provincial Marine Affairs and Fisheries with the actors, stake holders and the society; and, adequate human resources with competences required. On the other hand, the inhibiting factors include: the otocratic task managers and authority-compliance of the operational level officials level give negative impacts; incomplete and undetailed division of work and SOP gives negative impacts to the program implementation.